2017
DOI: 10.1158/0008-5472.can-17-1525
|View full text |Cite
|
Sign up to set email alerts
|

SOCS1 Gene Therapy Improves Radiosensitivity and Enhances Irradiation-Induced DNA Damage in Esophageal Squamous Cell Carcinoma

Abstract: STAT3 has been implicated recently in radioresistance in cancer. In this study, we investigated the association between STAT3 and radioresistance in esophageal squamous cell carcinoma (ESCC). Strong expression of activated phospho-STAT3 (p-STAT3) was observed in 16/22 ESCC patients with preoperative chemoradiotherapy (CRT), compared with 9 of 24 patients with surgery alone, where the prognosis of those with CRT was poor. Expression of p-STAT3 and the antiapoptotic proteins Mcl-1 and survivin was strongly induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Over the past decades, the emerging role of ncRNAs, including miRNAs, have been reported in the development of EC radioresistance. [28][29][30][31] In this study, we proved that miR-1275, which has been revealed to exert paradoxical functions in different cancer types, 12,[32][33][34] was down-regulated in radioresistant EC cells. Meanwhile, we illustrated that miR-1275 could increase the sensitivity of EC cells to radiotherapy both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…Over the past decades, the emerging role of ncRNAs, including miRNAs, have been reported in the development of EC radioresistance. [28][29][30][31] In this study, we proved that miR-1275, which has been revealed to exert paradoxical functions in different cancer types, 12,[32][33][34] was down-regulated in radioresistant EC cells. Meanwhile, we illustrated that miR-1275 could increase the sensitivity of EC cells to radiotherapy both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…Gene therapy strategies are also under development to re-express SOCS1 or SOCS3 in tumors [140][141][142].…”
Section: The Suppressor Of Cytokine Signaling Socsmentioning
confidence: 99%
“…GIST cells were plated in 96-well plates at a density of 2 × 10 3 cells per well and incubated for 24 h. Cell proliferation was evaluated using the Cell Counting Reagent SF (Nacalai Tesque) at the indicated times, as previously described [14,15]. The following inhibitors were used in this study: Imatinib (Novartis Pharmaceuticals, Basel, Switzerland), JAK inhibitor I (Calbiochem), FAK inhibitor (TAE226, Novartis Pharmaceuticals), and PI3 K inhibitor (LY294002, Cell Signaling Technology, Danvers, MA, USA).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…GIST cell lines were harvested and lysed as previously described, [14,15] and proteins were separated according to standard procedures. The following antibodies were used: anti-phospho (p)-KIT (Tyr703), anti-p-AKT (Thr308), anti-p-AKT (Ser473), anti-AKT, anti-p-p44/42 MAPK, anti-p44/42 MAPK, anti-p-STAT3, and anti-Cleaved-Caspase3 (1:1000 dilution) were from Cell Signaling Technology (Danvers, MA, USA); anti-KIT and anti-STAT3 (1:1000 dilution), and anti-glyceraldehyde 3-phosphate dehydrogenase (GAPDH, 1:2000 dilution) were from Santa Cruz Biotechnology (Santa Cruz, CA, USA); anti-SOCS1 (1:2000 dilution) was from IBL (Fujioka, Japan); anti-p-FAK (Tyr397) and anti-FAK (1:1000 dilution) were from BD Transduction Laboratories (San Jose, CA, USA).…”
Section: Western Blotting Analysismentioning
confidence: 99%
See 1 more Smart Citation